PELATIHAN PENERJEMAHAN POSTER DI KAMPUNG WISATA BAHARI TAMBAK LOROK SEMARANG - Mytha Candria (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
ABSTRAKDalam artikel ini, penulis membahas kegiatan pengabdian kepada masyarakat (PKM) yang bertujuan memberikan pelatihan kepada masyarakat di Kampung Wisata Bahari Tambak Lorok, Semarang Utara, untuk menerjemahkan teks poster dari bahasa Indonesia ke bahasa Inggris. Kegiatan pengabdian dilaksanakan pada bulan Mei 2019 dan difokuskan pada penerjemahan poster promosi pariwisata. Penerjemahan dilakukan dengan menggunakan model penerjemahan interlingual (interlingual translation) atau translation proper dari Eugene Nida. Hasilnya, peserta pelatihan dapat menerjemahkan poster-poster pariwisata sederhana dari bahasa Indonesia ke dalam bahasa Inggris. Kata kunci: Tambak Lorok; penerjemahan; poster; kampung wisata bahari. ABSTRACT This article centers upon the acts of community service that we conducted in Tambak Lorok, Semarang, in May 2019; the community service was aimed at teaching the people of Tambak Lorok Semarang to translate Indonesian posters into English. Tambak Lorok has since 2016 been projected into a maritime tourist destination by the government of Indonesia, and this is the reason the people of Tambak Lorok find it necessary to learn simple English. Learning English can done through various ways, one of which is through poster translation. The translation method used during the community service was interlingual translation or translation proper, as is proposed by Eugene Nida. The translation process includes three stages, namely analysis, transfer, and restructuring. The result of the community service is that the people of Tambak Loro who participated in the community service were able to translate simple tourism posters from Indonesian into English. Keywords: Tambak Lorok; translation; poster; maritime tourist destination.